1987
DOI: 10.1111/j.1365-4362.1987.tb00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination in Cutaneous Leishmaniasis I. Subcutaneous Nodules

Abstract: In a study of cutaneous leishmaniasis (CL) caused by Leishmania major in Saudi Arabia, 10% of the patients were found to have subcutaneous nodules (SCN). The SCNs were usually inconspicuous, painless, and proximal to the primary skin lesions; when multiple, they showed a "sporotrichoid" configuration or appeared as "beaded cords." Their number ranged from 1-16 (average 3 25 +/- 2.50; mean +/- 1 SD). In some patients, the SCNs seemed to be triggered by antileishmanial treatment. The clinical picture and patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
1
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 11 publications
0
57
1
1
Order By: Relevance
“…major infection is variable and includes nodular, ulcerative, and satellite lesions, lymph node enlargement, and lymphadenitis and lymphangitis with sporotrichoid spread. [12][13][14][15] The picture differs in various parts of the world in relation to the locally circulating L . major strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…major infection is variable and includes nodular, ulcerative, and satellite lesions, lymph node enlargement, and lymphadenitis and lymphangitis with sporotrichoid spread. [12][13][14][15] The picture differs in various parts of the world in relation to the locally circulating L . major strain.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from Saudi Arabia on L. major infections suggested that development of satellite lesions and lymphatic involvement may be related to treatment. 12,13,22 Treatments reported in these studies are local therapies (cryotherapy, ilSb v ) and systemic treatments, both oral (ketoconazole, rifampicin) and parenteral (antimony), but numbers of patients treated and specific relationships and associations of lymphatic involvement with respective treatments are not given. In a Cochrane analysis on treatment of Old World CL 19 and in a large series of ilSb v treatments of patients infected with L. tropica in Turkey, 23,24 lymphatic involvement during treatment is not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all strains from the Middle East were classified as expressing high (n ϭ 5) or intermediate (n ϭ 2) virulence whereas the majority of those from Tunisia were expressing low (n ϭ 4) or intermediate (n ϭ 6) virulence, with only two strains from this country expressing high virulence. Whether these differences in the experimental pathogenicity, induced by strains from North Africa or the Middle East, are germane to differences in the clinical severity of disease in humans is unknown; however, it is worth noting that ZCL due to L. major has globally a more benign evolution in Tunisia than in the Middle East (3,21). Thus, at El Guettar, where almost all Tunisian strains used in this study were collected, a prospective follow-up of ZCL previously showed that 65% of cutaneous lesions had spontaneously improved after 2 weeks and almost all of them had completely healed after 15 weeks (28).…”
Section: Discussionmentioning
confidence: 99%
“…Failure of the immune system to control parasite multiplication might lead to infection in the superficial layer of the papillary dermis in the eczematoid, erysipeloid, and psoriasiform forms or in the reticular dermis in sporotrichoid forms of CL (2). Multiple lesions of LCL can occur because of multiple inoculations by infected sand flies but can also result from parasite dissemination (130). A chronic form of LCL develops in cases where the protective response is insufficient and lesions persists for over 1 year (2).…”
Section: Cl-hiv Coinfectionmentioning
confidence: 99%